2011
DOI: 10.1016/j.renene.2010.06.008
|View full text |Cite
|
Sign up to set email alerts
|

A sensorless control for a variable speed wind turbine operating at partial load

Abstract: This paper presents a sensorless control for a variable speed wind turbine (WT) operating at partial load in order to eliminate the direct measurement of the wind speed. In this proposal, the estimated aerodynamic torque is used to determine the optimal reference of the speed control for maximum energy conversion. The maximization of the efficiency on energy conversion and the minimization of detrimental dynamical loads are control trade-offs considered in the design of an optimal discrete-time feedback LQG/LT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(18 citation statements)
references
References 26 publications
0
17
0
1
Order By: Relevance
“…El cortocircuito en parques eólicos puede presentarse cuando una ráfaga de viento atraviesa el aerogenerador ocasionando inestabilidad y disminuyendo la confiabilidad del parque; las protecciones eléctricas juegan un rol importante en la estabilidad del sistema al realizar la desconexión del sistema eléctrico (Rocha, 2011).…”
Section: Cortocircuitos En Aerogeneradores En Presencia De Ráfagas Deunclassified
“…El cortocircuito en parques eólicos puede presentarse cuando una ráfaga de viento atraviesa el aerogenerador ocasionando inestabilidad y disminuyendo la confiabilidad del parque; las protecciones eléctricas juegan un rol importante en la estabilidad del sistema al realizar la desconexión del sistema eléctrico (Rocha, 2011).…”
Section: Cortocircuitos En Aerogeneradores En Presencia De Ráfagas Deunclassified
“…The successive quadratic estimator (SQE) is selected as the optimum seeking algorithm. Although there are many optimization techniques in the literature [31][32][33], the advantage of this algorithm over conventional methods, such as the golden section search and simplex, is that no initial cost function values or bounds on the functional values are required [34]. The estimator approximates the cost function,P aero (ω(t)), as a quadratic function over a local bound and successively uses this property to predict the location of the optimum rotor speed, ω * .…”
Section: Trajectory Generation and Optimum Seeking Algorithmmentioning
confidence: 99%
“…After utilizing the fact that ω(t) ∈ L∞, from Assumption 6, it is apparent that f ( · ) ∈ L∞. After using Remarks 3 and 6 and the fact that e(t) ∈ L∞, along with (31), it can be shown that τ d (t) ∈ L∞. Remark 5 can be used along with the facts that…”
Section: A2 Proof Of Theoremmentioning
confidence: 99%
“…In [12] fuzzy logic control has been proposed and the effective wind speed is estimated using sequential Monte Carlo simulator. Discrete time optimal LQR/LTR based on optimal quadratic function is studied in [13]. In [14] the effective wind speed is estimated by the frequency domain data fusion and the observer is formulated based on the mixed sensitivity problem with linear matrix Inequalities.…”
Section: Introductionmentioning
confidence: 99%